Pengaruh Penggunaan Media Pembelajaran Online Terhadap Prestasi Belajar Siswa Kelas 5 SD - M Rizky Djanggola; Arif Firmansyah; Pahriadi Pahriadi (JURNAL BANUA OGE TADULAKO, 2022)
The research entitled "The Influence of the Use of Online Learning Media on the Learning Achievement of Class V Students at MIN Buol". This study aims to determine the effect of using online learning media on the learning achievement of fifth grade students at MIN Buol. The hypothesis in this study is that there is a significant effect between the use of online learning media on the learning achievement of fifth grade students at MIN Buol. The results of data analysis regarding the effect of using online learning media on student learning achievement where r count is 0.631> 0.374, meaning the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This means that there is a significant correlation between the effect of using online learning media (Variable X) and learning achievement (Variable Y). At a significant level of 5%, the research hypothesis reads "there is an effect of using online learning media on the learning achievement of fifth grade students at MIN Buol. The frequency of using online learning media on the learning achievement of fifth grade students at MIN Buol shows the results with a percentage of 8.392% and is classified as very high. The learning achievement of fifth grade students at MIN Buol based on the test obtained a percentage of 8.478% with a very good classification.